An investigation into the promotion of productive learning dispositions in government policies and teacher assessment in Grade R and Grade 1 - Long, Roxanne (Rhodes University, Faculty of Education, Department of Education, 2015)
The impetus for this study came from the increasing acknowledgement of learning dispositions as a central, yet largely under explored area of numeracy learning, in both international education literature and in the current work conducted by the South African Numeracy Chair, based at Rhodes University. This coupled with my own personal interest in the crucial transitional phase between Grade R (the year before formal schooling) and Grade 1 and the role of developing progressively strengthened learning dispositions, particularly in relation to numeracy learning, to enable this transition. This, together with the lack of research around what constitutes a quality Grade R programme, especially in South Africa, inspired an investigation into the promotion of key productive learning dispositions within current government policy and in teacher assessment practices across Grade R and Grade 1 in six local schools. I designed a qualitative research study underpinned by a socio-cultural theoretical perspective that foregrounds learning. Within this broad theoretical perspective I drew on two key analytic frameworks that cohere with this socio cultural view that prioritises learning dispositions (ways of being, habits of mind). In particular the work of Kilpatrick et al. (2001) and Carr & Claxton (2010), in defining essential elements of key productive learning dispositions, were combined to enable the development of an indicator matrix used for the analysis of current government policy and teacher assessment practices in the Grade R and Grade 1. Additionally empirical data from the study enabled extension and adaptation of the indicator matrix derived from key literature. The research contributes an analysis of various curriculum and policy documents across Grade R and 1 in terms of the inclusion and promotion of learning dispositions. The presences of certain promoted dispositions are compared with international literature and frameworks and certain absences or under represented dispositions are noted. The empirical data derived from Gr R and Gr 1 teacher questionnaires and exemplar reports across 6 schools are analysed and related back to policy. Similarities and differences across teachers in different grades and teachers in different schools are discussed. The findings point towards several avenues of research and also provide an emergent dispositional discourse from empirical data, policy analysis and literature that could enable engagement between various stakeholders around the notion of learning dispositions as a central feature of schooling in the Grade R to Grade 1 transition. It is argued from the data that the inclusion of exemplar reports, in teacher assessment policy guides, which indicate possible ways to communicate dispositional priorities to both parents and learners, would assist teachers in achieving greater coherence between dispositions promoted in the classroom and those assessed and reported on.
Keywords: Learning, Psychology of; Early childhood education -- Evaluation; Learning -- Evaluation; Educational psychology